Role for Macrophage Inflammatory Protein 2 (MIP-2), MIP-1α, and Interleukin-1α in the Delayed-Type Hypersensitivity Response to Viral Antigen - Tumpey, Terrence M. (American Society for Microbiology, 2002)
BALB/c mice sensitized to herpes simplex virus type 1 (HSV-1) develop a vigorous delayed-type hypersensitivity (DTH) response upon intradermal virus antigen challenge. Although CD4(+) T cells are a key mediator of this response, neutrophils are the most abundant cells at the antigen challenge site both initially and at the peak of the reaction. We investigated what role, if any, neutrophils play in the DTH to a viral antigen. We show here that antibody-mediated depletion of neutrophils 1 day before antigen challenge significantly suppressed ear swelling and markedly reduced cellular influx. Additionally, neutrophil depletion was associated with decreased expression of macrophage inflammatory protein 2 (MIP-2) and MIP-1α, as well as with a >60-fold increase in HSV-1 replication. Neutralizing antibodies to neutrophil chemoattractants MIP-2 or MIP-1α but not KC significantly suppressed DTH and sharply reduced neutrophil accumulation in the ear pinna. Purified bone marrow-derived neutrophils exposed to interleukin-1α (IL-1α) produced chemokines in an 8-h assay. Administration of neutralizing antibody to IL-1α significantly reduced ear swelling and suppressed the levels of MIP-2, MIP-1α, MIP-1β, and RANTES. We conclude that neutrophils are a critical component of the DTH response to viral antigen. They are recruited to the DTH test site by MIP-2 and MIP-1α, where they can be activated by IL-1α. The infiltrating cells also help suppress virus replication in immunized mice.